Empiric Antibiotics for Serious Bacterial Infection in Young Infants. Issue 8 (August 2015) - Cantey, Joseph B.; Lopez-Medina, Eduardo; Nguyen, Sean; Doern, Christopher; Garcia, Carla
<x xml:space="preserve">Abstract</x> Objectives To evaluate the causative agents of serious bacterial infection (SBI) in young infants and the optimal approach to empiric antibiotic therapy for infants with SBI. Methods From May 1, 2011, to December 1, 2013, pertinent clinical data were collected on previously well infants 60 days or younger with SBI as defined by a positive bacterial culture from a sterile site. Infants were identified by prospective surveillance of admissions and daily review of microbiology records. Results Two hundred sixty-five infants with SBI were identified. Mean age was 32 days (SD ±16.6 days). Twenty-nine infants had meningitis, 66 had bacteremia (37 with concomitant urinary tract infection), and 170 had urinary tract infection alone. No methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus sp., or penicillin-resistant Streptococcus pneumoniae were identified. Four extended-spectrum β-lactamase–producing gram-negative bacilli were seen. Empiric therapy was ampicillin and gentamicin (n = 116, 44%) or third-generation cephalosporin based (n = 149, 56%). Ampicillin and gentamicin, with third-generation cephalosporins reserved for cases where meningitis is suspected, would have provided effective coverage for 98.5% of infants and unnecessarily broad therapy for 4.3%. Third-generation cephalosporins with ampicillin would have been effective for 98.5% of infants and unnecessarily broad for 83.8%. Third-generation cephalosporin monotherapy was less effective than either combination (P < 0.001). Fifty-seven percent of broad spectrum empiric therapy was continued despite culture results allowing de-escalation. Conclusions Ampicillin/gentamicin remains an effective empiric regimen for infants 60 days or younger with suspected SBI. Use of a third-generation cephalosporin for suspected meningitis is appropriate, but cerebrospinal fluid must be obtained promptly to guide appropriate therapy.